Imported Machinery for Export Competitiveness - Mody, Ashoka (Washington, DC: World Bank, 2014)
This article analyzes the relationship between export competitiveness and investment in machinery, allowing for imperfect substitution between domestically produced and imported machinery. A trans log export price function is estimated for developed, export oriented developing, and import substituting developing economies in a panel data setting. Between 1967 and 1990 imported machinery helped lower export prices for export oriented developing economies. Moreover, throughout the period imported machinery was not a substitute for domestic machinery. Import substituting developing economies was unable to harness imported machinery to reduce costs early in the period, but from about the early 1980s, with the opening of their trade regimes, they were able to benefit from the cost reducing effect. The results imply that innovative effort based on imported technologies can be a precursor to the development of domestic innovation capabilities.